The 24th International Conference of Public Health Sciences "Public health 360 : From policy to practice", October 8, 2024, Mandarin Hotel, Bangkok, Thailand - International Conference of Public Health Sciences (24th: 2024 : Bangkok, Thailand) (College of Public Health Sciences, Chulalongkorn University, 2024)
194 pages